Separation of crude oil emulsions via microwave heating technology - Ser Er, Chang (2012)
Enhancement of separation process involving liquid-liquid or solid-liquid can be achieved using microwave irradiation technology.The traditional ways of breaking emulsions include heating and chemical are disadvantageous both from economic and environmental perspectives.In this thesis, the microwave potentials in demulsification of water-in-crude oil emulsions are investigated.The study began with some characterization of w/o emulsions such as formation, formulation,stabilization and breaking of emulsions to provide fundamental understanding of crude oil emulsions. The aim was to obtain optimized operating conditions as well as fundamental understanding of water-in-oil emulsions,upon which further developments on demulsification processes can be developed.The stability studies were carried out by analyzing operating condition such as stirring time, surfactant concentration,temperature,water-oil ratios (50-50% and 20-80%) and agitation speed (500rpm,1000rpm and 1500rpm).Four emulsifiers namely:Span 80,Span 83,Cocamide MEA and Triton X-100 were used for w/o stabilizations.It was found that they exist a correlations between these factors and emulsion stability.For microwave power applied (720 watts,540 watts and 360 watts),it conclude that the microwave power was proportional to the volume rate of heat generation and rate of temperature increase.Results show that microwave radiation can enhance the demulsification rate by order of magnitude.The result obtained in this study has exposed the capability of microwave technology in demulsification of water-in-oil emulsions.Further work is nevertheless required to provide deeper understanding of the mechanisms involved to facilitate the development of optimum system applicable to the industries.